The trend and interest in sports cycling during the Covid-19 pandemic - Fatoni, M.; Jariono, G.; Subroto, S.; Triadi, C. (Medikora, 2021)
The requirement for healthy breathing and maintaining body immunity defense is getting higher with the pandemic, mindfulness of the importance point of maintaining health and body immunity has become a new mindset approach in society. One of the efforts and hard works considered effective by the society to achieve realize in good physical nature and fit condition is by exercising. One of the sport that has many benefits is cycling. The perseverance of this study was to analyze trend and interest in society cycling during the pandemic. This research is quantitative descriptive. The research subjects were taken using purposive random sampling technique. The totally subjects studied in this study research were 130 people, which were divided into four groups (genres) of bicycles, namely BMX, Roadbike, Mountain Bike and Trial. In this research focuses in collected data. Data were collected using cross-sectional surveys using a Likert scale. The results of this research study are that there are 65 samples in the high category and get a percentage value of 50.00%, 63 samples in the medium category get a percentage value of 48.46%, and 2 samples in the less category get a percentage value of 1.54. %. Meanwhile, of the three types of bicycle genres that have the highest trend are road bikes with 62 respondents, then mountain bikes with 44 respondents, BMX and Trial with 12 respondents each. The conclusion of this study is that road bikes are the most trending genre among the public and the public interest in cycling during the Covid-19 pandemic is in the high category.